Importance of TFEB acetylation in control of its transcriptional activity and lysosomal function in response to histone deacetylase inhibitors. Issue 6 (3rd June 2018) - Zhang, Jianbin; Wang, Jigang; Zhou, Zhihong; Park, Jung-Eun; Wang, Liming; Wu, Shuai; Sun, Xin; Lu, Liqin; Wang, Tianru; Lin, Qingsong; Sze, Siu Kwan; Huang, Dongsheng; et al.
ABSTRACT: TFEB (transcription factor EB) is a master regulator of lysosomal biogenesis, function and autophagy. The transcriptional activity of TFEB is mainly controlled by its phosphorylation status mediated by the MTOR (mechanistic target of rapamycin [serine/threonine kinase]) complex 1 (MTORC1). At present, little is known whether other forms of posttranslational modifications (PTMs) such as acetylation also affects is transcriptional activity. In this study, we first observed that a well-established histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) activated lysosomal function in human cancer cells, a process independent of the MTORC1 pathway. Second, SAHA treatment activated TFEB transcriptional activity, as evidenced by increased TFEB luciferase activity and expression of its target genes. Third and more importantly, we observed the enhanced TFEB acetylation in SAHA-treated cells, with identification of 4 acetylation sites. Mutation of these 4 sites markedly diminished TFEB transcriptional activity and lysosomal function induced by SAHA. Finally, we found that TFEB acetylation was functionally implicated in SAHA-mediated autophagy and cell death in cancer cells. Taken together, our results demonstrate that TFEB acetylation is a novel form of PTMs in TFEB that plays an important role in determining its transcriptional activity, lysosomal function and autophagy in cancer cells. Abbreviations: ACAT1: acetyl-coenzyme A acetyltransferase 1; AHA: L-azidohomoalanine; AO: acidic orange; ATG: autophagy related; CLEAR: Coordinated Lysosomal Expression and Regulation; CQ: chloroquine; CTSB: cathepsin B; HATs: histone acetyltransferases; HDACIs: HDACs inhibitors; HDACs: histone deacetylases; IP: immunoprecipitation; MEFs: mouse embryonic fibroblasts; MS: mass spectrometry; MTOR: mechanistic target of rapamycin (serine/threonine kinase); MTORC1: mechanistic target of rapamycin (serine/threonine kinase) complex 1; PTMs: posttranslational modifications; SAHA: suberoylanilidehydroxamic acid; TFEB: transcription factor EB